Pengaruh Person-Job Fit dan Person-Organization Fit Terhadap Kinerja Karyawan PT. Sumatraco Langgeng Makmur - Sayuga, Hadad Dinanjar; Ambarwati, Arie; Fatmawati, Rini (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2023)
This research is motivated by facts or phenomena that are happening at this time, namely the fit between personality and work (Person-Job Fit) and the fit between personality and company environment/culture (Person-Organization Fit) which still influence employee performance at PT. Sumatraco Langgeng Prosperous. This study uses a quantitative approach and the type of research used is explanation/relationship. The sample used in this study amounted to 225 respondents. The results of this study using multiple regression methods can be concluded that partially the person-job fit variable has a significant influence on employee performance with a significance value of 0.000 <0.05 and also tcount (5.577) > ttable (1.972). Meanwhile, the person-organization fit variable also has a significant influence on employee performance with a significance value of 0.000 <0.05 and tcount (3.941) > ttable (1.972). Simultaneously the variables person-job fit and person-organization fit have a significant effect on employee performance with a significance value of 0.000 <0.05 and also the value of Fcount (42.088) > Ftable (4.7)